Diagnostic challenge: Intraventricular schwannoma masquerading as an ependymoma - Fahde Youssef; Imane Boujguenna; Dahmane Elhairech (Radiology Case Reports)
Intraventricular schwannomas are rare and benign tumors, typically located in peripheral nerves, especially the vestibular nerve. When they occur in the cerebral ventricles, these tumors are particularly unusual, with only 9 documented cases to date. One such case is reported in this article, involving a 10-year-old boy who presented with a seizure, leading to the discovery of an intraventricular mass at the right ventricular junction. After diagnostic evaluation and surgical intervention, the tumor was completely removed, with no postoperative complications. Although surgical management of intraventricular schwannomas is often effective and allows for recovery, their diagnosis remains challenging due to the lack of specific imaging signs. Standard imaging, such as MRI, may confuse these tumors with other brain masses, making early identification difficult. The etiopathogenesis of these tumors remains controversial, and several hypotheses have been proposed to explain their formation, though none have been confirmed. Despite these diagnostic challenges, surgical excision remains the treatment of choice and leads to good outcomes, although further research is needed to better understand the origin of these rare tumors.